The relationship between traditional and contemporary Islamist political thought - Kirmanj, Sherko (The Global Research in International Affairs (GLORIA) Center, 2008)
This article discusses links between the political theories and ideas of medieval and modern Islamists, showing how the latter is a continuation of the former’s writings.It also shows how episodes of Islamist thought have coincided with both external conflicts with non-Muslim powers and internal ones with local regimes.